Evaluación del porcentaje de leche de soya, edulcorante y lecitina sobre la viscosidad y las características organolépticas de una bebida láctea - Vidal Moreira, Luis Alexander (2013)
The aim of the research was to assess the percentage of soy milk, sweetener and lecithin on viscosity and organoleptic characteristics of milk beverage, in order to determine the best combination of ingredients. It was used a completely randomized design in accordance to trifactorial AxBxC, with three replicates per treatment. Three factors were manipulated in the study: A. Percentages of soy milk (50% and 40%) of the total combination of soy milk and cow milk, B. Types of sweeteners (aspartame and acesulfame K 0.025% 0.025%) and C Percentage of lecithin (0.3% and 0.4%), the experimental unit volume was 500 ml. The witness that was used was yogurt. Sensory characteristics were evaluated by scoring test, appearance, aroma, flavor, texture and overall quality by a panel of 25 trained tasters. Kinematic viscosity was determined by the free fall of a spherical body in the milk beverage in a known length. The best treatment was T6 (a2b2c1), which presented the highest scores in appearance with a 4.96, 5.36 flavor and texture to 5.04; obtaining a qualifier in general good, the same that had the highest m2/seg 0.6863 viscosity. By statistical analysis the variable viscosity, it was determined that there was no interaction between factors: Soy milk percentages, Rates and percentages of Lecithin sweeteners, but there were highly significant differences acting separately the factors of soymilk percentages and percentages of lecithin.